The effectiveness of antibacteria substances from neem seeds (Azadirachta indica) to impede the growth of Salmonella thyposa and Staphylococcus aureus - AMBARWATI AMBARWATI (Biodiversitas Journal of Biological Diversity, 2007)
Neem (Azadirachta indica) is a multifunction plant. Its leaves and seeds can be used as a traditional medicine. One of the benefits of neem seeds is that they can serve as antibacteria. It happens because neem seeds contain certain substances which can impede the growth of Salmonella thyposa and Staphylococcus aureus bacteria. The aims of this research were to find out the efectiveness of soaking neem seed powder in hampering the growth of Salmonella thyposa and Staphylococcus aureus bacteria and to find out the active chemistry compound in soaking neem seed powder based on the result of Tin Layer Cromatografi (TLC). It was an experimental research. Paper disc method was used to find out the impeding ability of soaking neem seed powder toward both kinds of bacteria. The effective concentration is shown by the existence of the biggest barrier area in that concentration. Based on the result of this research, it was known that the barrier’s diameter (didn’t include the paper disc’s diameter ) at Salmonella thyposa is as follow : soaking neem seed powder with 0% concentration (control) = 0 mm, 10.5% = 2.33 mm, 11.5% = 3.0 mm, 12.5% = 18.67 mm, 13.5% = 5.33 mm, 14.5% = 5.0 mm, and15.5% = 4.0 mm. While the barrier’s diameter at Staphylococcus aureus is as follow : soaking neem seed powder with 0% concentration (control) = 0 mm, 10.5% = 2.0 mm, 11.5% = 2.83 mm, 12.5% = 19.67 mm, 13.5% = 4.0 mm, 14.5% = 3.0 mm, 15.5% = 5 mm. Based on qualitative test result with TLC, it was found that the active chemistry compound in soaking neem seed powder are saponin and flavonoid. Based on this result, it can be concluded that soaking neem seed powder can impede the growth of Salmonella thyposa and Staphylococcus aureus.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Neem (Azadirachta indica), Barrier, Salmonella thyposa and Staphylococcus aureus, Paper disc, TLC